Punching shear analysis of slab-column connections - Moreno, Carlos (2013)
The paper aims to present an experimental testing program regarding reinforced concrete slabs, with and without shear reinforcement, submitted to punching under both symmetric and eccentric loading. Comparisons between numerical simulations and experimental behaviour results are carried on. The capabilities and limitations of the numerical model to reproduce the brittle punching-shear failure are discussed. The paper opted for a performance assessment of a numerical model, comparing FEM results with known experimental tests properly instrumented. Capability of DIANA software to simulate the punching behaviour of slabs is discussed. The paper demonstrates that the mechanical properties assigned to the element layer containing the bending reinforcement impose the load deflection stiffness behaviour. Good agreement was found between the predicted and the observed deformation behaviour. Nevertheless, the reproduction of the punching ultimate capacity is strongly dependent on the adopted value for the shear retention factor, which appears to be the major decisive parameter. This paper demonstrates that the smeared crack model based on both the concept of strain decomposition (SD) and total strain with fixed orthogonal cracks approach (TSF) can correctly be used for the analysis of the behaviour of slabs submitted to punching shear.